PHYTOEXTRACTION OF CADMIUM AND LEAD BY SELECTED CULTIVARS OF Tagetes erecta L. PART I. EFFECT OF Cd AND Pb ON YIELDING - Maciej Bosiacki (Acta Scientiarum Polonorum: Hortorum Cultus, 2009)
The objective of the presented studies carried out in the Department of Horticultural Plant Fertilization, University of Life Sciences in Poznań was the investigation of the influence of the introduced doses of cadmium and lead (soil pollution) on the yield of the particular organs of selected cultivars of Marigold (Tagetes erecta L.) and to check whether these plants are suitable to be planted on soils polluted with the mentioned metals. Plants used in the experiment were planted in individual outflowless containers in plastic tunnel. The studied cultivars of Marigold were planted in a substrate artificially polluted with cadmium and lead. The two heavy metals were introduced in the following doses: Cd – 0 (control); 1; 5; 10 mg dm-3, Pb – 0 (control); 100; 500; 1000 mg dm-3. Statistical analyses carried out in the present paper refer to the analysis of variance for leaf, stalk and inflorescence matters and the number of inflorescences. Analysis of the mean total yield of the particular cultivars grown in all substrates has shown that the highest total yield was reached by ‘Titania’ cultivar, in the second place was ‘Hawaii’ and the smallest yield was obtained from ‘Mann im Mond’. The smallest amounts of cadmium and lead, regardless of the applied dose, remained in the substrate in which ‘Hawaii’ cultivar was grown.